MHC class II-associated invariant chain isoforms regulate pulmonary immune responses. - Ye, Q; Finn, P; Sweeney, R; Bikoff, E; Riese, R (2003)
Asthma, a chronic inflammatory disease of the lung, is characterized by reversible airway obstruction and airway hyperresponsiveness (AHR), and is associated with increased production of IgE and Th2-type cytokines (IL-4, IL-5, and IL-13). Development of inflammation within the asthmatic lung depends on MHC class II-restricted Ag presentation, leading to stimulation of CD4(+) T cells and cytokine generation. Conventional MHC class II pathways require both MHC-associated invariant chain (Ii) and HLA-DM (H2-M in mice) chaperone activities, but alternative modes of Ag presentation may also promote in vivo immunity. In this study, we demonstrate that Ii(-/-) and H2-M(-/-) mice fail to develop lung inflammation or AHR following sensitization and challenge with OVA in a mouse model of allergic inflammation. To assess potentially distinct contributions by Ii chain isoforms to lung immunity, we also compared allergen-induced lung inflammation, eosinophilia, IgE production, and AHR in mice genetically altered to express either p31 Ii or p41 Ii isoform alone. Sole expression of either Ii isoform alone facilitates development of allergen-induced lung inflammation and eosinophilia. However, animals expressing only the p31 Ii isoform exhibit abrogated IgE and AHR responses as compared with p41 Ii mice in this model of allergen-induced lung inflammation, suggesting that realization of complete immunity within the lung requires expression of p41 Ii. These findings reveal a crucial role of Ii and H2-M in controlling the immune response within the lung, and suggest that p31 Ii and p41 Ii manifest nonredundant roles in development of immunity.